2018
DOI: 10.1002/cctc.201800707
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐Atomic Fe Centers in Nitrogen/Carbon Monolayers for Liquid‐Phase Selective Oxidation Reaction

Abstract: Two-dimensional catalyst supports with mono-atomic transition metals stabilized in special surface pockets conceptually promise excellent catalytic activity. Similar heterogenized monoatomic metal-based catalysts usually suffer from poor stability in liquid-phase reaction system, whilst highly ligand-stabilized metal-centers are less accessible for reactions. We report a twodimensional mono-atomic Fe/N/C layered nanostructure (2D-FeNC), generated through the direct polycondensation of C,N-containing molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Recently, N-doped carbon-supported metal catalysts have received widespread attention since N dopants can enhance the electronic interaction between metal and carbon support, alter the acid–base properties of the support surface, and therefore, increase the catalytic activity. Li et al prepared a N-functionalized mesoporous carbon-supported Pd catalyst by postsynthesis treatment with NH 3 or melamine. When this catalyst was used in the hydrogenation of phenol, a ∼80% conversion of phenol and a ∼100% selectivity to cyclohexanone were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, N-doped carbon-supported metal catalysts have received widespread attention since N dopants can enhance the electronic interaction between metal and carbon support, alter the acid–base properties of the support surface, and therefore, increase the catalytic activity. Li et al prepared a N-functionalized mesoporous carbon-supported Pd catalyst by postsynthesis treatment with NH 3 or melamine. When this catalyst was used in the hydrogenation of phenol, a ∼80% conversion of phenol and a ∼100% selectivity to cyclohexanone were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Benzyl alcohol as a vital raw material is a kind of extremely popular chemical reactant in many catalytic reactions, which can be converted into various products, such as aldehydes, esters, amines . In fact, it has been demonstrated that benzaldehyde could be obtained by selectively oxidizing benzyl alcohol with some oxidants such as H 2 O 2 , KMnO 4 , CrO 3 , and O 2 . ,, Among them, O 2 is an optimal choice due to environmental and energy crisis, which is a cheap and environmentally friendly oxidant . However, there are still many challenges since high-efficiency, stable, and cheap catalysts are urgently needed …”
Section: Introductionmentioning
confidence: 99%
“…To date, some metal-based materials played a more and more important role in heterogeneous catalysis, such as Fe-based, Co-based, and Ni-based catalysts. It has been demonstrated that mesoporous metal-based materials possess widely applications owing to the large superficial area and porosity, which were widely used as microwave absorbers, electrode materials, , sensors, , and catalysts, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former method, the chlorinated by-products and corresponding toxic acidic would be generated, which brought troubles to the industrial application (Mal et al, 2018;Lu et al, 2019), while the vapor/liquid oxidation of toluene was also limited because of the harsh reaction conditions and low selectivity (Miao et al, 2016). Recently, BzH production with benzyl alcohol oxidation was widely adopted in industry, based on its advantages of easy-control condition and high yield (Lv et al, 2018;Thao et al, 2018). In this method, potassium permanganate (KMnO 4 ) (Mahmood et al, 1999) and dichromate (K 2 Cr 2 O 7 ) (Thottathil et al, 1986) with a strong oxidizing property are chosen as oxidants.…”
Section: Introductionmentioning
confidence: 99%